2005
DOI: 10.1051/rnd:2005045
|View full text |Cite
|
Sign up to set email alerts
|

Effect of randomized supplementation with high dose olive, flax or fish oil on serum phospholipid fatty acid levels in adults with attention deficit hyperactivity disorder

Abstract: -Dietary intake of omega-3 fatty acids has been positively correlated with cardiovascular and neuropsychiatric health in several studies. The high seafood intake by the Japanese and Greenland Inuit has resulted in low ratios of the omega-6 fatty acid arachidonic acid (AA, 20:4n-6) to eicosapentaenoic acid (EPA,, with the Japanese showing AA:EPA ratios of approximately 1.7 and the Greenland Eskimos showing ratios of approximately 0.14. It was the objective of this study to determine the effect of supplementatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 54 publications
(58 reference statements)
1
22
0
1
Order By: Relevance
“…We are liable to believe that systemic DHA administration is helpful to improve the overall condition of diabetic rats. It has been reported that fish oil supplementation increased EPA and DHA in serum (Young et al, 2005), which suggested that DHA may have direct effect on the DRG neurons. In the present study, DHA was administrated intrathecally and attenuated pain behaviors of diabetic rats, which may be associated with its direct effect on modulating the neuron excitability.…”
Section: Discussionmentioning
confidence: 97%
“…We are liable to believe that systemic DHA administration is helpful to improve the overall condition of diabetic rats. It has been reported that fish oil supplementation increased EPA and DHA in serum (Young et al, 2005), which suggested that DHA may have direct effect on the DRG neurons. In the present study, DHA was administrated intrathecally and attenuated pain behaviors of diabetic rats, which may be associated with its direct effect on modulating the neuron excitability.…”
Section: Discussionmentioning
confidence: 97%
“…FO inhibited the subunits of NF-κB entering the nucleus and decreased the NF-κB level in the nucleus, and NF-κB maintained in the cytoplasm as an inactive form, which contributed to decreased inflammatory cytokines. It has been reported that FO supplementation increased EPA and DHA in serum [39], and DHA performed the neuroprotective effect on hippocampal neurons by its antioxidant effect, preventing inflammatory cytokine expression, and anti-apoptotic potential [40]. FO supplementation is also liable to exert effects on the DRGs directly.…”
Section: Discussionmentioning
confidence: 99%
“…The real answer could be given based on pharmacokinetic studies with RJ, but such literature data are lacking. However, based on the content of fatty acids in RJ [19], therapeutic doses of RJ exhibiting the immunomodulatory activity in rats [14] including our results that 3,10-DDA inhibited the KLH-induced immune response in vivo and pharmacokinetics of other fatty acids [39][40][41], it can be concluded that our in vitro results might be relevant in vivo.…”
Section: Discussionmentioning
confidence: 76%